Changes in cystic fibrosis transmembrane conductance regulator protein expression prior to and during elexacaftor-tezacaftor-ivacaftor therapy - Stanke, Frauke; Pallenberg, Sophia T.; Tamm, Stephanie; Hedtfeld, Silke; Eichhorn, Ella M.; Minso, Rebecca; Hansen, Gesine; Welte, Tobias; Sauer-Heilborn, Annette; Ringshausen, Felix C.; Junge, Sibylle; Tümmler, Burkhard; et al. (Frontiers in Pharmacology, 2023)
Background: Defects in expression, maturation or function of the epithelial membrane glycoprotein CFTR are causative for the progressive disease cystic fibrosis (CF). Recently, molecular therapeutics that improve CFTR maturation and functional defects have been approved. We aimed to verify whether we could detect an improvement of CFTR protein expression and maturation by triple therapy with elexacaftor-tezacaftor-ivacaftor (ELX/TEZ/IVA). Methods: Rectal suction biopsies of 21 p.Phe508del homozygous or compound heterozygous CF patients obtained pre- and during treatment with ELX/TEZ/IVA were analyzed by CFTR western blot that was optimized to distinguish CFTR glycoisoforms. Findings: CFTR western immunoblot analysis revealed that – compared to baseline – the levels of CFTR protein increased by at least twofold in eight out of 12 patients upon treatment with ELX/TEZ/IVA compared to baseline (p < 0.02). However, polydispersity of the mutant CFTR protein was lower than that of the fully glycosylated wild type CFTR Golgi isoform, indicating an incompletely glycosylated p.Phe508el CFTR protein isoform C* in patients with CF which persists after ELX/TEZ/IVA treatment. Interpretation: Treatment with ELX/TEZ/IVA increased protein expression by facilitating the posttranslational processing of mutant CFTR but apparently did not succeed in generating the polydisperse spectrum of N-linked oligosaccharides that is characteristic for the wild type CFTR band C glycoisoform. Our results caution that the lower amounts or immature glycosylation of the C* glycoisoform observed in patients’ biomaterial might not translate to fully restored function of mutant CFTR necessary for long-term provision of clinical benefit. Clinical Trial Registration at https://clinicaltrials.gov/; NCT04732910